Molecular marker analysis reveals Yellow berry tolerance loci on chromosomes 2D and 5D in bread wheat (Triticum aestivum L.) - Prashant, Ramya; Kulkarni, Krishnanand P; Dholakia, Bhushan B; Lagu, Meena D; Kadoo, Narendra Y; Dhaliwal, Harcharan Singh; Gupta, Vidya S. (Journal of Cereal Research, 2011)
Yellow berry (YB) is a physiological kernel disorder in wheat, which manifests as yellow, mottled, non-vitreous and starchy kernels. It occurs due to deficient soil nitrogen levels and affects milling and end-product quality of wheat. Genetic control of this disorder and association of some of the chromosomes with YB tolerance has been shown previously. However, the location of genes associated with YB tolerance on such chromosomes was not known. In view of this, we developed a simple sequence repeat marker based linkage map of hexaploid wheat using a recombinant inbred line population that segregated for YB tolerance and mapped the YB-linked genes on two wheat chromosomes. A major gene associated with YB was mapped on the short arm of chromosome 5D. In addition, a minor locus on chromosome 2D was detected that showed 6.9% contribution to the phenotypic variance in YB. The markers associated with the major gene for YB could be used for developing better varieties of wheat by molecular breeding.